Water Regime Monitoring of the Royal Walnut (Juglans regia L.) Using Sap Flow and Dendrometric Measurements - Viliam Bárek; Martina Kováčová; Vladimír Kišš; Oleg Paulen (Plants, 2021)
Changes in the distribution of annual rainfall totals, together with the increase in temperature over the last 40 years, are causing more frequent periods of drought, and plants are more often exposed to water stress. The aim of this study was to monitor the effect of different water regimes (irrigated and non-irrigated) of individuals of walnut tree (Juglans regia L.) in a private orchard located in the West of Slovakia. Our research was focused on dendrometric and sap flow measurements in the period from 28 March to 2 June 2019. The results showed differences in the sap flow of walnut trees during the budbreak period: when trees were irrigated, sap flow in the diurnal cycle was around 130 g·h−1 (20.48%), higher than in the non-irrigated treatment. Dendrometric differences between the irrigated and non-irrigated treatments were not significant. The sap flow data in the flowering period of the irrigated variant were slightly higher at 150 g·h−1 (35.62%) than non-irrigated. Dendrometric differences were more significant when the difference between the variants was more than 1.5 mm. Continuation of this research and analysis of the data obtained in the coming years will allow us to evaluate the effects of the environment on fruit trees in the long term.